Enhancing Communicative Competence in Generation Z Linguistic Students Through Reflective Methods - Zhukova T.A.; Satina T.V; Ganeeva E.R.; Akhmadeev D.R.; Chernykh P.A. (Ilmu Inovasi Nusantara, 2025)
This article explores the use of reflective methods as a pedagogical tool to develop communicative competence among linguistics students from Generation Z. The study highlights the need to adapt teaching strategies to the characteristics of modern university students, who often struggle with superficial information processing and reduced emotional intelligence. Reflective methods offer a promising solution by encouraging deeper cognitive engagement, metacognitive awareness, and critical thinking skills essential for communicative competence. Using a mixed-methods approach, the research combines theoretical analysis with empirical investigation. The theoretical framework is grounded in the CEFR model, which identifies the pragmatic component as the most challenging for students. The empirical phase involved a three-stage intervention—diagnostic, formative, and control—conducted with first-year linguistics students at NUST MISIS, Russia. A targeted set of tasks was developed based on four selected reflective methods to address weaknesses identified during the diagnostic stage. Pre- and post-test assessments of impromptu speech revealed significant improvement, with over half of the participants enhancing their performance. These results confirm the effectiveness of reflective methods in fostering communicative competence and suggest that the task model presented in this study can serve as a practical framework for addressing the communicative challenges specific to Generation Z learners